2017
DOI: 10.1128/aem.02319-16
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of OLE1 Enhances Cytoplasmic Membrane Stability and Confers Resistance to Cadmium in Saccharomyces cerevisiae

Abstract: The heavy metal cadmium is widely used and released into the environment, posing a severe threat to crops and humans. Saccharomyces cerevisiae is one of the most commonly used organisms in the investigation of environmental metal toxicity. We investigated cadmium stress and the adaptive mechanisms of yeast by screening a genome-wide essential gene overexpression library. A candidate gene, OLE1, encodes a delta-9 desaturase and was associated with high anti-cadmiumstress activity. The results demonstrated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 56 publications
(63 reference statements)
0
41
0
Order By: Relevance
“…Increased stearic acid levels in S. cerevisiae have been observed in previous studies that aimed to increase oleic acid levels to cope with membrane stress caused by with aliphatic alcohols (Yazawa et al, ; You et al, ), as well as exposure to 0.5 and 0.8 mM octanoic acid (Liu et al, ) and 35 μM of decanoic acid (Alexandre et al, ). However, it is important to note that this is a simplified analysis of lipid composition effects on the cell that does not consider the impact of lipids on membrane proteins, the presence of microdomains on cell membrane organization and dynamics (Marguet et al, ; Rest et al, ), as well as other regulatory mechanisms involved in the cell response to stress (Fang et al, ; Legras et al, ; Nasutution et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased stearic acid levels in S. cerevisiae have been observed in previous studies that aimed to increase oleic acid levels to cope with membrane stress caused by with aliphatic alcohols (Yazawa et al, ; You et al, ), as well as exposure to 0.5 and 0.8 mM octanoic acid (Liu et al, ) and 35 μM of decanoic acid (Alexandre et al, ). However, it is important to note that this is a simplified analysis of lipid composition effects on the cell that does not consider the impact of lipids on membrane proteins, the presence of microdomains on cell membrane organization and dynamics (Marguet et al, ; Rest et al, ), as well as other regulatory mechanisms involved in the cell response to stress (Fang et al, ; Legras et al, ; Nasutution et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the changes in fatty acid composition, it was hypothesized that modification of membrane rigidity activates the cell's stress response mechanism leading to increased proton efflux, diminished membrane damage, and lower levels of ROS (Nasutution et al, ). Higher oleic acid levels were also found to ameliorate cadmium‐related stresses by promoting cytoplasmatic membrane stability via inhibition of lipid peroxidation (Fang et al, ). These studies demonstrate that modulation of fatty acid composition results in increased membrane stability.…”
Section: Introductionmentioning
confidence: 99%
“…TAG biosynthesis involves several genes from the lipid metabolic pathway, including those encoding the delta-9 desaturase ( OLE1 ) and the diacylglyceride acyl-transferase ( DGA1 ) [14, 15], and it has been demonstrated that regulating these two genes dramatically affect lipid composition of the cell [16, 17]. In both examples, increased productivity of isoprenoids and TAGs need to be balanced by cell membrane integrity and growth.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Fig. A, the strain overexpressing OLE1 exhibited a slight increase in the percentage of not only monounsaturated fatty acids (mono‐UFAs) but also UFAs compared with those of the blank control strain ( P < 0.05), which is consistent with the findings in previous studies (Fang et al ., ; Nasution et al ., ). However, the knockdown of OLE1 had no significant effect on fatty acid composition.…”
Section: Resultsmentioning
confidence: 97%
“…At high temperatures, the generation of reactive oxygen species (ROS) is enhanced significantly as a result of heat stress (Morano et al ., ), leading to lipid peroxidation that triggers cytoplasmic membrane damage (Tsaluchidu and Puri, ; Morano et al ., ). It is thought that UFAs may play an antioxidant role (Fang et al ., ). In a recent study, Fang et al .…”
Section: Resultsmentioning
confidence: 99%